Drug-related problems among breastfeeding patients treated for depressive spectrum disorders - Morze, Karolina; Szałek, Edyta; Waszyk-Nowaczyk, Magdalena (Frontiers in Pharmacology, 2024)
Introduction Depressive spectrum disorders are common and can hinder breastfeeding success. While medications typically pose minimal risk, the concerns persist. This is the first study that investigates the prevalence and characteristics of drug-related problems among breastfeeding mothers with depressive spectrum disorders. We analyzed those problems to understand their nature, severity, and contributing factors. Additionally, we evaluated the outcomes of pharmacist-led interventions in reducing them. Understanding drug-related problems is crucial for informing evidence-based practices to optimize both maternal mental health and breastfeeding success. Materials and methods This prospective observational study was conducted at a specialized pharmacy office in Poznan, Poland, which focuses on lactation support and medication consultations. 47 breastfeeding patients were enrolled. Pharmaceutical consultations were conducted according to Joint Commission of Pharmacy Practitioners Pharmacists’ Patient Care Process standards. Novel MILC Questionnaire was used for efficient and optimal pharmaceutical interview. Drug-related problems were assessed basing on PCNE Classification System version 9.1. For adverse events in lactation, MedDRA v27 nomenclature was used; for causality, Naranjo Scale and LCAT were utilized. CTCAE was used for grading. Results Among the 47 patients, pharmacist identified 49 medication-related problems, with inadequate treatment effect due to underdosing or not taking the medication at all being the most common (57.1%). Pharmacist interventions focused on medication safety information and counseling. Overall, 78.7% of patients accepted these interventions, resulting in problem resolution for 71.4%. Twelve mothers (25.5%) reported adverse events in their infants, but after causality evaluation, only four (8.5%) might have been linked to maternal medication. None required medical intervention beyond one hospitalization for a serious adverse event possibly connected to maternal medication. Conclusion The study identified high rates of drug-related problems among breastfeeding mothers with depression, primarily due to non-adherence. Pharmacist interventions significantly improved DRP outcomes. Adverse events were reported, but most were mild and did not require intervention. Our findings suggest that lactating mothers with depressive spectrum disorders may benefit from pharmacist-led support to optimize treatment adherence and address medication safety concern.